Permafrost Landscape History Shapes Fluvial Chemistry, Ecosystem Carbon Balance, and Potential Trajectories of Future Change - Zolkos, Scott; Tank, Suzanne E.; Kokelj, Steven V.; Striegl, Robert G.; Shakil, Sarah; Voigt, Carolina; Sonnentag, Oliver; Quinton, William L.; Schuur, Edward A. G.; Zona, Donatella; Lafleur, Peter M.; Sullivan, Ryan C.; et al. (Global biogeochemical cycles, 2022)
Intensifying permafrost thaw alters carbon cycling by mobilizing large amounts of terrestrial substrate into aquatic ecosystems. Yet, few studies have measured aquatic carbon fluxes and constrained drivers of ecosystem carbon balance across heterogeneous Arctic landscapes. Here, we characterized hydrochemical and landscape controls on fluvial carbon cycling, quantified fluvial carbon fluxes, and estimated fluvial contributions to ecosystem carbon balance across 33 watersheds in four ecoregions in the continuous permafrost zone of the western Canadian Arctic: unglaciated uplands, ice‐rich moraine, and organic‐rich lowlands and till plains. Major ions, stable isotopes, and carbon speciation and fluxes revealed patterns in carbon cycling across ecoregions defined by terrain relief and accumulation of organics. In previously unglaciated mountainous watersheds, bicarbonate dominated carbon export (70% of total) due to chemical weathering of bedrock. In lowland watersheds, where soil organic carbon stores were largest, lateral transport of dissolved organic carbon (50%) and efflux of biotic CO2 (25%) dominated. In watersheds affected by thaw‐induced mass wasting, erosion of ice‐rich tills enhanced chemical weathering and increased particulate carbon fluxes by two orders of magnitude. From an ecosystem carbon balance perspective, fluvial carbon export in watersheds not affected by thaw‐induced wasting was, on average, equivalent to 6%–16% of estimated net ecosystem exchange (NEE). In watersheds affected by thaw‐induced wasting, fluvial carbon export approached 60% of NEE. Because future intensification of thermokarst activity will amplify fluvial carbon export, determining the fate of carbon across diverse northern landscapes is a priority for constraining trajectories of permafrost region ecosystem carbon balance. Plain Language Summary Freshwaters are a main component of the global carbon cycle and climate. Yet, their role in climate change is uncertain in permafrost regions, where thaw is releasing large amounts of carbon and enabling production of climate‐warming greenhouse gases. To reduce uncertainty, we measured stream chemistry and carbon fluxes across four ecoregions including a global hotspot of permafrost thaw in the western Canadian Arctic. Comparing across ecoregions, lowlands were strong sources of biological carbon dioxide and methane to the atmosphere; mountain rivers ferried products from chemical rock weathering downstream; and streams affected by permafrost thaw‐induced wasting transported large amounts of particulate carbon. Typical of northern ecosystems, carbon fluxes in non‐thaw‐affected streams were equivalent to 6%–16% of carbon uptake by terrestrial vegetation. However, in watersheds affected by thaw‐induced wasting, carbon fluxes were up to 100 times higher and approached 60% of vegetation carbon uptake. Together, these findings reveal that thermokarst‐susceptible terrains are poised to emerge as a significant component of the Arctic ecosystem carbon balance and global climate feedbacks, due to hydrologic carbon fluxes that will intensify as permafrost thaw accelerates. Key Points Permafrost landscape history regulates fluvial carbon (C) sources and export across a transect of continental glaciation and thermokarst Fluvial C flux equaled 6%–16% of vegetation C uptake in most watersheds and 60% in those affected by permafrost thaw‐driven mass wasting Thaw‐susceptible terrains will be significant to Arctic ecosystem carbon balance as permafrost thaw and hydrologic carbon fluxes intensify